From Files to Databases: The Dynamics of Digitalization of Personnel Management in the Public Sector of Education - Haris maulana safari; Nurul Hikmah; Slamet Riyadi (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This research aims to examine the implementation of digital systems in personnel management in regional educational institutions, focusing on the organizational adaptation process and the challenges faced during the transition from manual to digital systems. Using a qualitative approach of case studies, data were collected through direct observation, semi-structured interviews with staff, and internal agency documentation. The results of the study show that the implementation of applications such as SIMPEG and Srikandi has significantly changed the pattern of personnel services, especially in digital archiving, online leave applications, and employee data validation. However, digitalization also faces various obstacles, ranging from limited networks and upload capacity to digital literacy gaps between generations of employees. Emerging adaptation strategies include intergenerational collaboration, informal mentoring, and the use of dual technologies (cloud and local devices) to anticipate systemic constraints. This study shows that the success of staffing digitization depends not only on infrastructure but also on the readiness of work culture, internal collaboration, and responsive strategies of bureaucratic actors. These findings make a theoretical contribution to the study of digital transformation in the public sector and have practical implications for local governments in designing inclusive and sustainable digitalization policies.